Strategi Pemasaran Produk-Produk Gadai Syariah Di Sumatera Utara - Arnida Wahyuni Lubis; Diana Loemongga Siregar (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2021)
Sharia pawnshops include non-bank financial institutions that are present in Indonesia in the form of syariah bank cooperation with Perum Pegadaian, then forming Sharia Pawn Service Units in several cities in Indonesia. Sharia pawning products are Rahn, Rahn Hasan, Rahn Tasjily Tanah, ArRum Emas, ArRum Haji, Mulia, ArRum BPKB, Amanah. Marketing strategy is an integrated plan to market a merchandise to the community. This research aims to first, find out how many customers in 2016, 2017 and 2018 who used EmasKu products; second, the marketing strategy carried out by PT Pegadaian Syariah Setia Budi Branch of Pegadaian; and third, knowing the obstacles experienced by PT Pegadaian Syariah Setia Budi Branch of Pegadaian. This research is a field research with a qualitative descriptive research method. The data collection technique was done by interviewing and collecting data. The object of the research is a non-bank financial institution, namely a pawnshop with a sharia system, namely PT Pegadaian Syariah Setia Budi Branch of Pegadaian. The results showed that the number of customers at PT Pegadaian Syariah Setia Budi Pegadaian Branch who used EmasKu products in 2016, 2017, 2018 amounted to 8 customers, 35 customers and 25 customers, although the number of customers each year continues to increase, the marketing strategy implemented by PT Setia Budi Sharia Pegadaian Branch, among others, applies the 4P principle, namely Product, Price, Place (Distribution or Place), and Promotion (Promotion), PT Pegadaian Syariah Setia Budi Pegadaian Branch experienced obstacles in implementing its marketing strategy, namely the existence of competitors who are Islamic financial institutions that have similar products.